APPLICATION OF THE ECODRAINAGE SYSTEM IN BINTANG ALAM HOUSING, KARAWANG REGENCY - Nike Murni Ananda Sari; Sih Andajani; Dina Paramitha Anggraeni Hidayat (International Journal on Livable Space, 2021)
Bintang Alam is housing area in Karawang regency which often occurs flood. Bintang Alam housing has a land area of 147,33 ha and located on the edge of the Citarum River downstream section. Therefore, it is necessary to have a good implementation and planning for the drainage system in Bintang Alam housing. The research aimed to find an effective way to prevent and solve floods in Bintang Alam. There are 2 scenarios that applied to the drainage planning at the Bintang Alam estate. Scenario 1, direct runoff from housing area is going directly to channel then the outlet point and for scenario 2, most of the flow entered to the soil through the infiltration wells then some of its flow into retention ponds. With the application of the two ecodrains, it is proven that they are able to reduce the planned flood discharge in the area with infiltration wells to reduce flood discharge by 25,96% and retention ponds to reduce flood discharge by 33,91%. Keywords: Citarum River, Drainage Channels, Karawang, Ecodrainage